(untitled) (Huellas, 2023)
The purpose of this study is to quantify and describe the different land uses present in the lower basin of the Lujan River, Buenos Aires Province, as well as to analyze the spatial evolution between 1990 and 2020. To do so, different land use coverages were identified by using visual interpretation techniques and satellite images. From this, digital thematic mapping was created for the two years under study. The methodology used was proposed by Pontius (2007), in which the cross-tabulation matrix was calculated and indicators of land use changes such as gain, loss, persistence, and swaps were computed. The results provide detailed information about the dynamics of change of the area under study or in different land use coverages.